Incidence of Thrombophlebitis Due to Venous Access: An Observational Study - Shaji, Ashli; B G, Harish; safadi, Ellen; Kandakurti, Praveenkumar; I Herakal, Gurulingappa; Baburaj, Aparnna (Journal of Neonatal Surgery, 2025)
Background: Peripheral venous cannulation (PVC) is a critical procedure for delivering fluids, medications, and blood products to hospitalized patients. However, thrombophlebitis remains a common complication. Aims: The aim of this study was to look at the effect of the cannula gauge, insertion site, and indwelling duration on thrombophlebitis incidence in order to enhance clinical practice and patient outcomes. Settings and Design: This prospective observational study, conducted from May 2021 to September 2022, included 90 adult participants undergoing elective surgery at a tertiary care hospital. Methods and Material: Following single-attempt cannulation with 18-gauge (18G) or 20-gauge (20G) PVCs in the median cubital, cephalic, or metacarpal veins, patients were monitored at 12 h, 24 h, 36 h, 48 h, and 72 h post-insertion with the use of the Visual Infusion Phlebitis (VIP) score. Chi-square tests were used to examine the data (P < 0.05 was considered significant). Results: Thrombophlebitis incidence was significantly influenced by the insertion site (χ² = 7.271, P = 0.026) and indwelling duration (χ² = 19.1498, P = 0.0039), but not by gauge (χ² = 0.4, P = 0.527). Cephalic veins had the lowest rate (33.3%), while metacarpal veins had the highest (70%). Incidence peaked at 24–36 h, with a mean duration of 3741.89 ± 1284.66 min (up to 6060 min). Age and gender showed no association. Conclusion: Preferring cephalic or median cubital veins and monitoring indwelling duration can reduce thrombophlebitis, enhancing patient safety and care quality